Implementasi Aquasmart And Wastewater Treatment Guna Meningkatkan Hasil Produksi pada Budidaya Ikan Bumdes Bio Avicenna Abyudaya Kabupaten Pekalongan - Elvinda Bendra Agustina; M. Rudi Fanani; Nasyita Vivi Amalia; Jessika Artamevira; Khusfiatul Kholisah (Yayasan Literasi Sains Indonesia, 2025)
The activities are based on the issues by the community in Api-Api village regarding the management of fish and shrimp ponds. These issues include the high cost of pond cultivation, inefficient feed provision, leading to wastefulness and a decrease in the Feed Conversion Ratio (FCR). Additionally, the liquid waste from the cultivation process has not been optimally utilized or managed, resulting in environmental pollution when disposed of directly, and many fish/shrimp dying due to poor water quality. Efforts have been made to provide solutions using the Aquasmart technology system: Smart Feeder Innovation and Water Quality Monitoring IoT (Internet of Things) and biofiltration technology with natural material wastewater treatment as a solution to the wastewater problems caused by feed materials and fish/shrimp waste.The activities were implemented in stages, starting with socializing and introducing the Aquasmart system and the use of simple biofilter wastewater treatment at the house of the headman of Api-Api. After that, the implementation of the Aquasmart system was carried out directly at the ponds managed by BUMDes (Village-Owned Enterprise) together with BUMDes members and the pond management community. The result showed that the community and BUMDes members reached new knowledge and skills related to pond management technology for fish and shrimp. The satisfaction level of the participants in the socialization and implementation of the activities showed above 50%, that indicating the participants were satisfied with the activities. The technology provided is expected to reduce the issues in pond management.